Water-based polyaniline polymer, preparation method thereof and anticorrosive paint
The aqueous polyaniline polymer prepared by the interfacial polymerization method uses tripolyphosphate ions and metal ions to form chelates, solving the problem of poor anticorrosion performance of existing water-based anticorrosion coatings, and achieving high adhesion and long-term anticorrosion properties.
Patent Information
- Application Number
- CN202510110528.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The anticorrosion performance of existing water-based anticorrosion coatings is poor and it is difficult to meet the long-term anticorrosion performance requirements. The neutral salt spray test only 120 hours ago showed problems such as bubbles, paint film peeling and severe rust of metal substrates.
Through the interfacial polymerization method, the aniline monomer is polymerized in situ on the inside and outside surface of aluminum trihydrogen tripolyphosphate sheet to prepare an aqueous polyaniline polymer. The tripolyphosphate ions of the polymer can form a chelate with metal ions, forming a protective film with stable performance, and improving the long-term anticorrosion performance of the coating.
The adhesion of anticorrosion coatings was improved to 13MPa, and the neutral salt spray experiment reached 2,000 hours, significantly improving the anticorrosion performance and meeting the requirements of long-term anticorrosion performance.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corrosion prevention, and in particular to a water-based polyaniline polymer, a preparation method thereof and an anticorrosive coating. Background Art
[0002] Green and environmentally friendly water-based anti-corrosion coatings refer to anti-corrosion coatings that use water as a solvent, do not contain harmful substances, and are harmless to the environment and human health. Green and environmentally friendly water-based anti-corrosion coatings that do not contain heavy metals such as lead and chromium have become a development trend in this field. The most representative of these is the zinc-based water-based anti-corrosion coating system. However, zinc ore, as a valuable mineral resource in my country, has a wide range of industrial value and application fields, and the demand for it in various fields is increasing. Therefore, the development of new water-based anti-corrosion coatings that do not rely on zinc powder has become a new development trend in the field of water-based anti-corrosion coatings.
[0003] The anti-corrosion performance of anti-corrosion coatings mainly depends on film-forming resins and anti-corrosion materials. Polyaniline has been widely recognized in the industry for its unique anti-corrosion mechanism and excellent performance. It has become an important anti-corrosion coating system in recent years and has been widely studied. However, the anti-corrosion performance of water-based anti-corrosion coating systems is still far behind that of solvent-based anti-corrosion coatings. After only 120 hours of neutral salt spray test, blistering, paint film shedding, and severe rust on the metal substrate appeared. The anti-corrosion performance is poor and it is difficult to meet the requirements of long-term anti-corrosion performance. Summary of the invention
[0004] In view of this, the present invention discloses a water-based polyaniline polymer, a preparation method thereof and an anti-corrosion coating. The tripolyphosphate ions in the water-based polyaniline polymer disclosed by the present invention can form a chelate with metal ions and form a protective film with stable performance on the metal surface, thereby improving the long-term anti-corrosion performance of the coating, increasing the adhesion to 13MPa, and the neutral salt spray test to 2000h.
[0005] The present invention provides an aqueous polyaniline polymer having a structure of formula (I):
[0006] (I);
[0007] Wherein, n is an integer from 1 to 500, 0<x<1, and y is an integer from 0 to 4;
[0008] R1 is selected from hydrogen, C1~C 10 Alkyl, C6~C 20 Aromatic or C6~C 20 heteroaryl;
[0009] R — The acid radical ion is selected from the group consisting of ethoxy repeating units.
[0010] In some specific implementations, the R1 is selected from hydrogen or C1~C 10 The alkyl group;
[0011] The R — Select from the following structures:
[0012] , , ;
[0013] m is an integer from 1 to 15.
[0014] The present invention provides a method for preparing a water-based polyaniline polymer, comprising:
[0015] a) an aniline compound represented by formula (II), an initiator and aluminum dihydrogen tripolyphosphate undergo a polymerization reaction to obtain a polyaniline compound;
[0016] b) mixing the polyaniline compound obtained in step a) with an aqueous dopant to undergo a modification reaction to obtain an aqueous polyaniline polymer represented by formula (I);
[0017] (II);
[0018] The aqueous dopant is selected from acids containing ethoxy repeating units;
[0019] (I);
[0020] Wherein, n is an integer from 1 to 500, 0<x<1, and y is an integer from 0 to 4;
[0021] R1 is selected from hydrogen, C1~C 10 Alkyl, C6~C 20 Aromatic or C6~C 20 heteroaryl;
[0022] R — The acid radical ion is selected from the group consisting of ethoxy repeating units.
[0023] In some specific implementations, the molar ratio of the aniline compound, the initiator and aluminum dihydrogen tripolyphosphate is (91-220): (67-400): (0.47-1.95);
[0024] The mass ratio of the aqueous dopant to the aniline compound is 1:0.3-3.
[0025] The present invention also provides a water-based anticorrosive coating, comprising component A and component B;
[0026] Wherein, the component A comprises the following components in parts by weight:
[0027] The above technical solution provides 0.5-4 parts of water-based polyaniline polymer, 20-120 parts of water-based epoxy resin, 5-20 parts of water, 10-30 parts of water-based film-forming cosolvent, 5-20 parts of titanium dioxide, 8-40 parts of talc, 3-15 parts of precipitated barium sulfate, 0.3-3 parts of water-based defoamer, and 0.4-3 parts of water-based dispersant;
[0028] The component B comprises the following components in parts by weight:
[0029] 65~90 parts of water-based epoxy curing agent; 0.3~0.7 parts of anti-flash rust agent.
[0030] In some specific implementations, the mass ratio of component A to component B is 1-5:1.
[0031] In some specific implementations, the waterborne epoxy resin is selected from at least one of Huntsman PZ3961-1, Shanghai Huayi STW606, Shanghai Huayi STW6521 and Shanghai Huayi STW6522.
[0032] In some specific implementations, the aqueous defoamer is selected from at least one of BYK-052, BYK-088, BYK-1752, BYK-053, BYK-051, BYK-057, BYK-077, BYK-066N, BYK-392, BYK-333, BYK-141 and BYK-1790.
[0033] In some specific implementations, the waterborne epoxy curing agent is selected from at least one of Huntsman AD3986, Huntsman AD3987, Huntsman AD38-1, Shanghai Huayi STW703C and Shanghai Huayi STW703D.
[0034] In some specific implementations, the aqueous dispersant is selected from at least one of Disperbyk-103, Disperbyk-108, Disperbyk-115, Disperbyk-130, Disperbyk-111, Disperbyk-180, Disperbyk-160, Disperbyk-162, Disperbyk-164 and Disperbyk-182.
[0035] The present invention provides a water-based polyaniline polymer, a preparation method thereof and an anti-corrosion coating. The present invention uses an interfacial polymerization method to make aniline monomers in situ polymerize inside and outside the sheet of aluminum dihydrogen tripolyphosphate, thereby preparing a water-based polyaniline polymer. The larger specific surface area of polyaniline fibers allows polyaniline to have a larger contact area on the metal surface, forming a larger area of passivation protective layer on the surface of the metal substrate, thereby improving the anti-corrosion performance. Experimental results show that when the water-based polyaniline polymer provided by the present invention is applied to the anti-corrosion coating, its adhesion on the surface of the metal substrate is increased to 13MPa, and the neutral salt spray reaches 2000h. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is the SEM image of aluminum dihydrogen tripolyphosphate;
[0037] Figure 2 is a SEM image of the waterborne polyaniline polymer prepared in Example 1;
[0038] Figure 3 This is a SEM image of the waterborne polyaniline polymer prepared in Example 2;
[0039] Figure 4 This is the SEM image of the water-based polyaniline polymer prepared in Comparative Example 1. DETAILED DESCRIPTION
[0040] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0041] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0042] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0043] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0044] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0045] The water-based polyaniline polymer provided by the present invention has a structure of formula (I):
[0046] (I);
[0047] wherein n is an integer of 1 to 500, preferably an integer of 10 to 50, more preferably an integer of 20 to 500; y is an integer of 0 to 4, preferably an integer of 0 to 3, more preferably an integer of 0 to 2; 0<x<1;
[0048] R1 is selected from hydrogen, C1~C 10 Alkyl, C6~C 20 Aromatic or C6~C 20 heteroaryl;
[0049] R — The acid radical ion is selected from the group consisting of ethoxy repeating units.
[0050] The present invention uses an interfacial polymerization method to make aniline monomers in situ polymerize inside and outside the sheet of aluminum tripolyphosphate, thereby preparing a water-based polyaniline polymer. The aluminum tripolyphosphate component contains tripolyphosphate ions (P3O 10 5- ), can form chelates with metal ions and form a stable protective film on the metal surface, which has good corrosion resistance for metals. Figure 1 The scanning electron microscope image of aluminum dihydrogen tripolyphosphate is shown, from which its lamella morphology can be clearly seen. The water-based polyaniline polymer provided by the present invention fully utilizes the passivation and anti-corrosion properties of aluminum dihydrogen tripolyphosphate and polyaniline, and greatly improves the anti-corrosion effect through the synergistic effect between the two.
[0051] In some specific implementations, the R1 is selected from hydrogen or C1~C 10 The alkyl group is preferably hydrogen.
[0052] The present invention uses phosphoric acid containing ethoxy repeating units or sulfonic acid containing ethoxy repeating units as an aqueous dopant to disperse polyaniline in water to obtain an aqueous polyaniline polymer. In some specific implementations, the R — Select from the following structures:
[0053] , , ;
[0054] m is an integer from 1 to 15.
[0055] The present invention provides a method for preparing the water-based polyaniline polymer, comprising:
[0056] a) an aniline compound represented by formula (II), an initiator and aluminum dihydrogen tripolyphosphate undergo a polymerization reaction to obtain a polyaniline compound;
[0057] b) mixing the polyaniline compound obtained in step a) with an aqueous dopant to undergo a modification reaction to obtain an aqueous polyaniline polymer represented by formula (I);
[0058] (II);
[0059] The aqueous dopant is selected from acids containing ethoxy repeating units;
[0060] (I);
[0061] Wherein, n is an integer from 1 to 500, 0<x<1, and y is an integer from 0 to 4;
[0062] R1 is selected from hydrogen, C1~C 10 Alkyl, C6~C 20 Aromatic or C6~C 20 heteroaryl;
[0063] R — The acid radical ion is selected from the group consisting of ethoxy repeating units.
[0064] The present invention first dissolves aluminum dihydrogen tripolyphosphate, an initiator and an aniline compound respectively and then undergoes a polymerization reaction to obtain a polyaniline compound. In some specific implementations, the solvent of the aluminum dihydrogen tripolyphosphate is selected from at least one of a water-soluble solvent and water. In some specific implementations, the solvent of the initiator is selected from at least one of an inorganic acid, a water-soluble solvent and water. In some specific implementations, the solvent of the aniline compound is a non-water-soluble solvent.
[0065] In some specific implementations, the water-soluble solvent is selected from at least one of methanol, ethanol, isopropanol, ethylene glycol ethyl ether, ethylene glycol butyl ether, ethylene glycol and glycerol; preferably at least one of methanol, ethanol and isopropanol, and more preferably at least one of methanol and isopropanol. In some specific implementations, the inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, acetic acid and carbonic acid, preferably at least one of hydrochloric acid, sulfuric acid and phosphoric acid, and more preferably hydrochloric acid. In some specific implementations, the non-water-soluble solvent is selected from at least one of carbon tetrachloride, chloroform, benzene, toluene and xylene, preferably at least one of carbon tetrachloride and chloroform, and more preferably carbon tetrachloride.
[0066] In some specific implementations, the molar ratio of the aniline compound, the initiator and aluminum dihydrogen tripolyphosphate is (91-220): (67-400): (0.47-1.95).
[0067] After obtaining the polyaniline compound, the present invention preferably immerses it in an alkaline solution to change the activation energy on its surface and increase the effect of the modification reaction. In some specific implementations, the alkaline solution is selected from one or more of ammonia water, triethylamine, sodium hydroxide solution, sodium bicarbonate solution, sodium carbonate solution, potassium bicarbonate solution and potassium hydroxide solution, preferably one or more of ammonia water, triethylamine, sodium hydroxide solution and sodium bicarbonate solution, more preferably ammonia water. In some specific implementations, the polyaniline compound is immersed in the alkaline solution for 18 to 36 hours at room temperature. After the polyaniline compound is soaked, it is washed with deionized water and dried to obtain a polyaniline compound powder.
[0068] The polyaniline compound powder, the aqueous dopant and water are mixed to undergo a modification reaction to obtain the aqueous polyaniline polymer.
[0069] In some specific implementations, the modification reaction is carried out under an inert atmosphere, preferably a nitrogen atmosphere or an argon atmosphere, more preferably a nitrogen atmosphere. In some specific implementations, the modification reaction time is 4 to 6 hours, and the temperature is 60 to 80° C. In some specific implementations, the mass ratio of the aqueous dopant to the aniline compound is 1:0.3 to 3.
[0070] The present invention preferably uses phosphoric acid containing ethoxy repeating units and sulfonic acid containing ethoxy repeating units as aqueous dopants for modification reaction. The present invention has no special restrictions on their sources, and they can be purchased or synthesized by themselves. For example, they can be prepared according to the method of Geng et al. (Polymer, 1999, 40, 5723-5727): phosphorus oxide or sulfur oxide and polyethylene glycol monomethyl ether are mixed uniformly in benzene to react at a reaction temperature of 50-90° C. for 2-5 hours to obtain the phosphoric acid containing ethoxy repeating units or the sulfonic acid containing ethoxy repeating units.
[0071] The present invention also provides a water-based anticorrosive coating, comprising component A and component B;
[0072] Wherein, the component A comprises the following components in parts by weight:
[0073] The above technical solution provides 0.5-4 parts of water-based polyaniline polymer, preferably 0.5-3.7 parts, more preferably 0.5-3.5 parts; also includes 20-120 parts of water-based epoxy resin, preferably 25-120 parts, more preferably 28-120 parts; also includes 5-20 parts of water, preferably 8-20 parts, more preferably 10-20 parts; also includes 10-30 parts of water-based film-forming co-solvent, preferably 12-30 parts, more preferably 15-30 parts; also includes 5 parts of titanium dioxide The invention also comprises 8 to 20 parts, preferably 5 to 17 parts, more preferably 5 to 15 parts; 8 to 40 parts, preferably 8 to 37 parts, more preferably 8 to 35 parts of talc; 3 to 15 parts, preferably 3 to 13 parts, more preferably 3 to 12 parts of precipitated barium sulfate; 0.3 to 3 parts, preferably 0.3 to 2.5 parts, more preferably 0.3 to 2 parts of aqueous defoaming agent; and 0.4 to 3 parts, preferably 0.4 to 2.5 parts, more preferably 0.4 to 2 parts of aqueous dispersant.
[0074] The component B comprises the following components in parts by weight:
[0075] 65-90 parts of waterborne epoxy curing agent, preferably 65-85 parts, more preferably 65-80 parts; 0.3-0.7 parts of anti-flash rust agent, preferably 0.3-0.6 parts, 0.3-0.5 parts.
[0076] The present invention adds the above-mentioned water-based polyaniline polymer to the anti-corrosion coating, fully utilizing the passivation anti-corrosion performance of aluminum dihydrogen triphosphate and polyaniline, and greatly improving the anti-corrosion effect through the synergistic effect between the two. Moreover, aluminum dihydrogen triphosphate is weakly acidic, and its dissociation constant pKa=1.5~1.6. Through the aniline monomer and the aniline monomer, the two substances are first combined together at the molecular level, and then the aniline is in-situ polymerized on aluminum dihydrogen triphosphate to form an aluminum dihydrogen triphosphate inorganic hybrid polyaniline composite material. Moreover, the relative density of aluminum dihydrogen triphosphate is relatively large, which is 2.31g / cm 3 , which is very easy to settle in water-based coatings and has poor compatibility with water-based resins. The composite material of the present invention organically combines aluminum dihydrogen tripolyphosphate and polyaniline, which can be well dispersed in water-based resins, and the density of polyaniline is relatively small, thereby avoiding the sedimentation problem of aluminum dihydrogen tripolyphosphate.
[0077] In some specific implementations, the mass ratio of component A to component B is 1-5:1.
[0078] Waterborne epoxy resin has excellent physical and mechanical properties, aging resistance, freeze-thaw resistance, corrosion resistance and other characteristics; at the same time, it has extremely strong waterproof performance and good chemical corrosion resistance, and can effectively prevent corrosion from chemical substances such as acids, alkalis, and salts. In some specific implementations, the waterborne epoxy resin is selected from one or more of Huntsman PZ3961-1, Shanghai Huayi STW606, Shanghai Huayi STW6521, and Shanghai Huayi STW6522. The present invention has no special requirements for the proportion of each substance.
[0079] The aqueous defoamer can be quickly dispersed in the coating system, effectively reduce liquid tension, destroy the stability of the foam, achieve rapid defoaming and prevent foam regeneration, significantly improve the construction performance of the coating, make the coating surface smooth and bubble-free, and improve the anti-corrosion performance. In some specific implementations, the aqueous defoamer is selected from one or more of BYK-052, BYK-088, BYK-1752, BYK-053, BYK-051, BYK-057, BYK-077, BYK-066N, BYK-392, BYK-333, BYK-141 and BYK-1790, and the present invention has no special requirements on the proportion of each substance.
[0080] The water-based epoxy curing agent can promote the rapid hardening of the coating surface, thereby accelerating drying; at the same time, it can significantly improve the hardness of the coating, making the coating more durable and wear-resistant. After the coating is applied, the curing agent will continue to play a role, so that the hardness and toughness of the coating surface are improved, thereby enhancing the protective ability of the coating. In some specific implementations, the water-based epoxy curing agent is selected from one or more of Huntsman AD3986, Huntsman AD3987, Huntsman AD38-1, Shanghai Huayi STW703C and Shanghai Huayi STW703D, and the present invention has no special requirements for the proportion of each substance.
[0081] The aqueous dispersant can effectively prevent the aggregation of particles of each component of the anti-corrosion coating, thereby ensuring that the coating forms a uniform and dense protective film on the metal surface, which can not only improve the anti-corrosion performance of the coating, but also extend the service life of the metal material. In some specific implementations, the aqueous dispersant is selected from one or more of Disperbyk-103, Disperbyk-108, Disperbyk-115, Disperbyk-130, Disperbyk-111, Disperbyk-180, Disperbyk-160, Disperbyk-162, Disperbyk-164 and Disperbyk-182, and the present invention has no special requirements on the proportion of each substance.
[0082] The flash rust preventer can prevent the flash rust phenomenon caused by environmental factors such as moisture and oxygen on the metal surface during or after the coating process. It can instantly shield metal ions or reduce the reactivity of metal ions through its special chemical composition, cut off or reduce the supply of oxygen, and effectively prevent the occurrence of flash rust. In some specific implementations, the flash rust preventer is selected from one or more of ASCOTEC H10, ASCOTEC H14, ASCOTEC H18 and Hemmingsdeqian FA179, and the present invention has no special requirements on the proportion of each substance therein.
[0083] The water-based film-forming aid can reduce the minimum film-forming temperature of the water-based epoxy resin, so that it can form a continuous and ideal coating film at a lower temperature; at the same time, by adjusting the drying speed, the hardness and anti-adhesion properties of the paint film are improved. In some specific implementations, the water-based film-forming aid is selected from one or more of ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol phenyl ether, dipropylene glycol methyl ether, propylene glycol butyl ether, dipropylene glycol butyl ether, dipropylene glycol propyl ether and propylene glycol, and the present invention has no special requirements for the proportion of each substance.
[0084] For the above-mentioned water-based anticorrosive coating, the present invention also provides a preparation method, which specifically comprises:
[0085] 1) After the water-based polyaniline polymer, water-based epoxy resin, water, titanium dioxide, talcum powder, precipitated barium sulfate and water-based dispersant are uniformly dispersed, the water-based film-forming aid and the water-based defoamer are added and stirred for 15 to 25 minutes, and filtered through a 60 to 100 mesh filter to obtain component A;
[0086] 2) Disperse the water-based epoxy curing agent and water evenly, then add the water-based film-forming aid and anti-flash rust agent, and continue stirring for 10 to 15 minutes to obtain component B.
[0087] The present invention provides a water-based polyaniline polymer, a preparation method thereof and an anti-corrosion coating. The present invention uses an interfacial polymerization method to make aniline monomers in situ polymerize inside and outside the sheet of aluminum dihydrogen tripolyphosphate to prepare a water-based polyaniline polymer. The larger specific surface area of polyaniline fibers allows polyaniline to have a larger contact area on the metal surface, forming a larger area of passivation protective layer on the surface of the metal substrate, thereby improving the anti-corrosion performance.
[0088] The present invention is further described below in conjunction with the following examples. The protection scope of the present invention is not limited by the following examples.
[0089] Example 1
[0090] (1) Weigh 0.35 g of aluminum dihydrogen tripolyphosphate, 80 g of isopropyl alcohol and 100 g of deionized water into a beaker and ultrasonicate for 2 hours to form an aqueous dispersion A;
[0091] (2) Add 38.5 g of ammonium persulfate to 300 ml of 1 mol / L hydrochloric acid solution, and add 120 g of methanol and 200 g of deionized water to the solution to prepare aqueous solution B; add aqueous dispersion A to aqueous solution B and stir for 10 min to obtain aqueous dispersion C;
[0092] (3) Add 14.9 g of aniline and 600 ml of carbon tetrachloride into a beaker and stir with electromagnetic stirring for 5 min to form an organic solution. Slowly pour the aqueous dispersion C into the organic solution along the wall of the beaker to form a stable interface between the two phases. Seal the mouth of the beaker with a polyethylene film and place it in an environment at 8°C for 24 h.
[0093] (4) The product obtained in step (3) was filtered through a G3 sand core funnel and washed with 150 ml of deionized water. This operation was repeated 5 times to obtain a solid powder after washing and filtration;
[0094] (5) The solid powder obtained in step (4) was added to 150 ml of ammonia water, stirred at room temperature for 20 min, soaked for 24 hours, filtered through a G3 sand core funnel, and washed with 300 ml of deionized water. This operation was repeated 8 times to obtain a polyaniline compound powder after washing and filtration;
[0095] (6) The polyaniline compound powder obtained in step (5) was placed in a three-necked flask, and 10.1 g of a phosphate aqueous dopant (the structure is as follows) and 320 ml of deionized water were added. Under nitrogen protection, the temperature was controlled at 60° C. and stirred for 6 hours to obtain an aqueous polyaniline solution.
[0096] (7) The aqueous polyaniline solution was centrifuged at 5000 rpm for 30 min to separate the aqueous solution, collect the solid, and place the solid in a vacuum oven at 40 °C for drying for 48 h to obtain an aqueous polyaniline polymer. Figure 2 Shown is the SEM electron microscope image of the water-based polyaniline polymer prepared in this example.
[0097]
[0098] The aqueous dopant structure of this embodiment
[0099] Example 2
[0100] (1) Weigh 0.62 g of aluminum dihydrogen tripolyphosphate, 180 g of ethanol and 200 g of deionized water into a beaker and ultrasonicate for 2 hours to form an aqueous dispersion A;
[0101] (2) Add 39.5 g of sodium persulfate to 350 ml of 1 mol·L-1 phosphoric acid solution, and add 160 g of ethanol and 240 g of deionized water to the solution to prepare aqueous solution B; add aqueous dispersion A to aqueous solution B and stir for 10 min to obtain aqueous dispersion C;
[0102] (3) Add 18.5 g of aniline and 550 ml of chloroform into a beaker and stir with electromagnetic stirring for 15 min to form an organic solution. Slowly pour the aqueous dispersion C into the organic solution along the wall of the beaker to form a stable interface between the two phases. Seal the mouth of the beaker with a polyethylene film and place it in an environment of 15°C for 24 h.
[0103] (4) The product obtained in step (3) was filtered through a G3 sand core funnel and washed with 300 ml of deionized water. This operation was repeated 5 times to obtain a solid powder after washing and filtration;
[0104] (5) Add 380 g of 40% sodium carbonate aqueous solution to the solid powder obtained in step (4), stir at room temperature for 30 min, soak for 24 hours, filter with a G3 sand core funnel, and wash with 500 ml of deionized water. Repeat this operation 8 times to obtain a polyaniline compound powder after washing and filtration;
[0105] (6) The polyaniline compound powder obtained in step (5) was placed in a three-necked flask, and 15.8 g of a phosphate aqueous dopant (the structure is as follows) and 320 ml of deionized water were added. Under nitrogen protection, the temperature was controlled at 80° C. and stirred for 4 hours to obtain an aqueous polyaniline solution.
[0106] (7) The aqueous polyaniline solution was centrifuged at 10,000 rpm for 20 min to separate the aqueous solution, and the solid powder was collected. The solid powder was placed in a vacuum oven at 50°C and dried for 24 h to obtain an aqueous polyaniline polymer. Figure 3 Shown is the SEM electron microscope image of the water-based polyaniline polymer prepared in this example.
[0107]
[0108] The aqueous dopant structure of this embodiment
[0109] Example 3
[0110] (1) Weigh 0.3 g of aluminum dihydrogen tripolyphosphate, 60 g of isopropyl alcohol and 140 g of deionized water into a beaker and ultrasonicate for 2 hours to form an aqueous dispersion A;
[0111] (2) Add 47.5 g of potassium dichromate to 420 ml of 1 mol·L-1 nitric acid solution, and add 180 g of ethylene glycol ethyl ether and 160 g of deionized water to the solution to prepare aqueous solution B; add aqueous dispersion A to aqueous solution B and stir for 8 min to obtain aqueous dispersion C;
[0112] (3) Add 13.5 g of aniline and 500 ml of benzene into a beaker and stir with electromagnetic stirring for 5 min to form an organic solution; slowly pour the aqueous dispersion C into the organic solution along the wall of the beaker to form a stable interface between the two phases. Seal the mouth of the beaker with a polyethylene film and place it in an environment of 10°C for 24 h.
[0113] (4) The product obtained in step (3) was filtered through a G3 sand core funnel and washed with 220 ml of deionized water. This operation was repeated 8 times to obtain a solid powder after washing and filtration;
[0114] (5) Add 280 ml of 30% sodium hydroxide solution to the solid powder obtained in step (4), stir at room temperature for 35 min, soak for 18 hours, filter through a G3 sand core funnel, and wash with 350 ml of deionized water. Repeat this operation 10 times to obtain a polyaniline compound powder after washing and filtration;
[0115] (6) The polyaniline compound powder obtained in step (5) was placed in a three-necked flask, and 20.6 g of a phosphate aqueous dopant (the structure is as follows) and 260 ml of deionized water were added. Under nitrogen protection, the temperature was controlled at 70° C. and stirred for 5 hours to obtain an aqueous polyaniline solution.
[0116] (7) The aqueous polyaniline solution was centrifuged at 8000 rpm for 30 min to separate the aqueous solution and collect the solid powder. The solid powder was placed in a vacuum oven at 40° C. and dried for 48 h to obtain an aqueous polyaniline polymer.
[0117]
[0118] The aqueous dopant structure of this embodiment
[0119] Example 4
[0120] (1) Weigh 0.55 g of aluminum dihydrogen tripolyphosphate, 85 g of ethylene glycol butyl ether and 115 g of deionized water into a beaker and ultrasonicate for 2 hours to form an aqueous dispersion A;
[0121] (2) Add 35.3 g of potassium iodate to 310 ml of 1 mol·L-1 carbonic acid, and add 150 g of ethylene glycol butyl ether and 160 g of deionized water to the solution to prepare aqueous solution B; add aqueous dispersion A to aqueous solution B and stir for 10 min to obtain aqueous dispersion C;
[0122] (3) Add 20.8 g of aniline and 450 ml of xylene into a beaker and stir with electromagnetic stirring for 8 min to form an organic solution; slowly pour the aqueous dispersion C into the organic solution along the wall of the beaker to form a stable interface between the two phases. Seal the mouth of the beaker with a polyethylene film and place it in an environment of 12°C for 24 h.
[0123] (4) The product obtained in step (3) was filtered through a G3 sand core funnel and washed with 170 ml of deionized water. This operation was repeated 7 times to obtain a solid powder after washing and filtration;
[0124] (5) Add 275 ml of 45% sodium bicarbonate solution to the solid powder obtained in step (4), stir at room temperature for 20 min, soak for 36 hours, filter through a G3 sand core funnel, and wash with 420 ml of deionized water. Repeat this operation 8 times to obtain a polyaniline compound powder after washing and filtration;
[0125] (6) The polyaniline compound powder obtained in step (5) was placed in a three-necked flask, and 22.5 g of a phosphate aqueous dopant (the structure is as follows) and 250 ml of deionized water were added. Under nitrogen protection, the temperature was controlled at 65° C. and stirred for 5.5 hours to obtain an aqueous polyaniline solution;
[0126] (7) The aqueous polyaniline solution was centrifuged at 7000 rpm for 35 min to separate the aqueous solution, and the solid powder was collected. The solid powder was placed in a vacuum oven at 40° C. and dried for 36 h to obtain an aqueous polyaniline polymer.
[0127]
[0128] The aqueous dopant structure of this embodiment
[0129] Example 5
[0130] (1) Weigh 0.15 g of aluminum dihydrogen tripolyphosphate, 50 g of ethylene glycol and 80 g of deionized water into a beaker and ultrasonicate for 2 hours to form an aqueous dispersion A;
[0131] (2) Add 64.7 g of ferric sulfate to 200 ml of 1 mol·L-1 sulfuric acid solution, and add 180 g of ethylene glycol and 140 g of deionized water to the solution to prepare aqueous solution B; add aqueous dispersion A to aqueous solution B and stir for 15 min to obtain aqueous dispersion C;
[0132] (3) Add 11.8 g of aniline and 400 ml of xylene into a beaker and stir with electromagnetic stirring for 5 min to form an organic solution; slowly pour the aqueous dispersion C into the organic solution along the wall of the beaker to form a stable interface between the two phases. Seal the mouth of the beaker with a polyethylene film and place it in an environment at 10°C for 24 h.
[0133] (4) The product obtained in step (3) was filtered through a G3 sand core funnel and washed with 200 ml of deionized water. This operation was repeated 6 times to obtain a solid powder after washing and filtration;
[0134] (5) Add 310 ml of triethylamine to the solid powder obtained in step (4), stir at room temperature for 16 min, soak for 36 hours, filter with a G3 sand core funnel, and wash with 200 ml of deionized water. Repeat this operation 10 times to obtain a polyaniline compound powder after washing and filtration;
[0135] (6) The polyaniline compound powder obtained in step (5) was placed in a three-necked flask, and 18.6 g of a sulfonate aqueous dopant (structure shown below) and 160 ml of deionized water were added. The temperature was controlled at 70° C. under nitrogen protection and stirred for 5 hours to obtain an aqueous polyaniline solution.
[0136] (7) The aqueous polyaniline solution was centrifuged at 3000 rpm for 30 min to separate the aqueous solution, and the solid powder was collected. The solid powder was placed in a vacuum oven at 45° C. and dried for 48 h to obtain an aqueous polyaniline polymer.
[0137]
[0138] The aqueous dopant structure of this embodiment
[0139] Example 6
[0140] (1) Weigh 0.6 g of aluminum dihydrogen tripolyphosphate, 200 g of ethylene glycol butyl ether and 150 g of deionized water into a beaker and ultrasonicate for 2 hours to form an aqueous dispersion A;
[0141] (2) Add 26.7 g of ferric chloride to 220 ml of 1 mol·L-1 hydrochloric acid solution, and add 160 g of ethylene glycol butyl ether and 100 g of deionized water to the solution to prepare aqueous solution B; add aqueous dispersion A to aqueous solution B and stir for 12 min to obtain aqueous dispersion C;
[0142] (3) Add 8.5 g of aniline and 300 ml of chloroform into a beaker and stir with electromagnetic stirring for 9 min to form an organic solution. Slowly pour the aqueous dispersion C into the organic solution along the wall of the beaker to form a stable interface between the two phases. Seal the mouth of the beaker with a polyethylene film and place it in an environment at 6°C for 24 h.
[0143] (4) The product obtained in step (3) was filtered through a G3 sand core funnel and washed with 170 ml of deionized water. This operation was repeated 8 times to obtain a solid powder after washing and filtration;
[0144] (5) Add 360 ml of 35% potassium bicarbonate aqueous solution to the solid powder obtained in step (4), stir at room temperature for 15 min, soak for 36 hours, filter through a G3 sand core funnel, and wash with 280 ml of deionized water. Repeat this operation 3 times to obtain a polyaniline compound powder after washing and filtration;
[0145] (6) The polyaniline compound powder obtained in step (5) was placed in a three-necked flask, and 24.9 g of a phosphate aqueous dopant (the structure is as follows) and 150 ml of deionized water were added. Under nitrogen protection, the temperature was controlled at 75° C. and stirred for 5.5 hours to obtain an aqueous polyaniline solution;
[0146] (7) The aqueous polyaniline solution was centrifuged at 5000 rpm for 30 min to separate the aqueous solution and collect the solid powder. The solid powder was placed in a vacuum oven at 50° C. and dried for 24 h to obtain an aqueous polyaniline polymer.
[0147]
[0148] The aqueous dopant structure of this embodiment
[0149] Comparative Example 1
[0150] In this comparative example, the aluminum dihydrogen tripolyphosphate component is removed in step (1), and the remaining steps are the same as those in Example 1 to obtain a polyaniline nanofiber material. Figure 4 Shown is the SEM electron microscope image of the water-based polyaniline polymer prepared in this comparative example.
[0151] Example 7
[0152] a) adding 0.5 g of waterborne polyaniline polymer (prepared in Example 1), 28 g of PZ3961-1, 10 g of deionized water, 5 g of titanium dioxide, 8 g of talc, 3 g of precipitated barium sulfate and 0.4 g of Disperbyk-108 into a high-speed disperser, stirring at a speed of 1400 rpm for 30 min, and then introducing into a sand milling tank for sand milling for 2 hours; after the sand milling, introducing the material into a high-speed disperser, adding 15 g of ethylene glycol butyl ether and 0.3 g of BYK-052, stirring at a speed of 700 rpm for 20 min, and filtering with a 80-mesh filter to obtain component A;
[0153] b) In a high-speed dispersing container, add 65 g AD3986 and 10 g deionized water, add 15 g ethylene glycol butyl ether and 0.3 g ASCOTEC H10 in sequence at 550 rpm, and continue stirring for 15 min to obtain component B; mix component A and component B in a ratio of 3:2 to obtain a water-based polyaniline anticorrosive coating PT01.
[0154] Example 8
[0155] a) 3.5 g of waterborne polyaniline polymer (prepared in Example 2), 120 g of STW606, 20 g of deionized water, 15 g of titanium dioxide, 35 g of talc, 12 g of precipitated barium sulfate and 2 g of Disperbyk-130 were added to a high-speed disperser, stirred at a speed of 1400 rpm for 30 min, and then introduced into a sand mill for sand milling for 2 hours; after the sand milling, the material was introduced into a high-speed disperser, 30 g of propylene glycol phenyl ether and 2 g of BYK-1752 were added, stirred at a speed of 700 rpm for 20 min, and filtered with a 80-mesh filter to obtain component A;
[0156] b) In a high-speed dispersion container, add 80 g of AD3987 and 20 g of deionized water, add 30 g of propylene glycol phenyl ether and 0.5 g of ASCOTEC H14 in sequence at 550 rpm, and continue stirring for 15 minutes to obtain component B; mix component A and component B in a ratio of 3:2 to obtain a water-based polyaniline anticorrosive coating PT02.
[0157] Example 9
[0158] a) 0.8 g of water-based polyaniline polymer (prepared in Example 3), 45 g of STW6522, 13 g of deionized water, 8 g of titanium dioxide, 17 g of talc, 6 g of precipitated barium sulfate and 0.7 g of Disperbyk-180 were added to a high-speed disperser, stirred at a speed of 1400 rpm for 30 min, and then introduced into a sand mill for sand milling for 2 hours; after the sand milling, the material was introduced into a high-speed disperser, 18 g of diethylene glycol butyl ether and 0.9 g of BYK-051 were added, stirred at a speed of 700 rpm for 20 min, and filtered with a 80-mesh filter to obtain component A;
[0159] b) In a high-speed dispersion container, add 70 g STW703D and 13 g deionized water, add 18 g diethylene glycol butyl ether and 0.4 g FA179 in sequence at 550 rpm, and continue stirring for 15 min to obtain component B; mix component A and component B in a ratio of 3:2 to obtain water-based polyaniline anti-corrosion coating PT03.
[0160] Example 10
[0161] a) 1.5 g of water-based polyaniline polymer (prepared in Example 4), 68 g of STW606, 15 g of deionized water, 10 g of titanium dioxide, 22 g of talc, 4 g of precipitated barium sulfate and 1.3 g of Disperbyk-130 were added to a high-speed disperser, stirred at a speed of 1400 rpm for 30 min, and then introduced into a sand mill for sand milling for 2 hours; after the sand milling, the material was introduced into a high-speed disperser, 22 g of propylene glycol phenyl ether and 1.4 g of BYK-1752 were added, stirred at a speed of 700 rpm for 20 min, and filtered through a 80-mesh filter to obtain component A;
[0162] b) In a high-speed dispersion container, add 75 g AD3987 and 15 g deionized water, add 22 g propylene glycol phenyl ether and 0.35 g ASCOTEC H14 in sequence at 550 rpm, and continue stirring for 15 min to obtain component B; mix component A and component B in a ratio of 3:2 to obtain water-based polyaniline anticorrosive coating PT04.
[0163] Embodiment 11
[0164] a) 3.0 g of water-based polyaniline polymer (prepared in Example 5), 85 g of PZ3961-1, 18 g of deionized water, 12 g of titanium dioxide, 15 g of talc, 10 g of precipitated barium sulfate and 1.5 g of Disperbyk-180 were added to a high-speed disperser, stirred at a speed of 1400 rpm for 30 min, and then introduced into a sand mill for sand milling for 2 hours; after the sand milling, the material was introduced into a high-speed disperser, 26 g of ethylene glycol butyl ether and 1.6 g of BYK-051 were added, stirred at a speed of 700 rpm for 20 min, and filtered through a 80-mesh filter to obtain component A;
[0165] b) In a high-speed dispersion container, add 78 g AD3986 and 18 g deionized water, add 26 g ethylene glycol butyl ether and 0.45 g ASCOTEC H10 in sequence at 550 rpm, and continue stirring for 15 minutes to obtain component B; mix component A and component B in a ratio of 3:2 to obtain water-based polyaniline anti-corrosion coating PT05.
[0166] Example 12
[0167] a) 2.6 g of water-based polyaniline polymer (prepared in Example 6), 105 g of STW606, 16 g of deionized water, 7 g of titanium dioxide, 30 g of talc, 9 g of precipitated barium sulfate and 1.8 g of Disperbyk-108 were added to a high-speed disperser, stirred at a speed of 1400 rpm for 30 min, and then introduced into a sand mill for sand milling for 2 hours; after the sand milling, the material was introduced into a high-speed disperser, 20 g of propylene glycol phenyl ether and 1.1 g of BYK-052 were added, stirred at a speed of 700 rpm for 20 min, and filtered through a 80-mesh filter to obtain component A;
[0168] b) In a high-speed dispersion container, add 72 g STW703D and 16 g deionized water, add 20 g propylene glycol phenyl ether and 0.5 g FA179 in sequence at 550 rpm, and continue stirring for 15 min to obtain component B; mix component A and component B in a ratio of 3:2 to obtain water-based polyaniline anti-corrosion coating PT06.
[0169] Comparative Example 2
[0170] Compared with Example 7, the difference is that 0.5 g of the water-based polyaniline polymer prepared in Comparative Example 1 is used instead of 0.5 g of the water-based polyaniline polymer prepared in Example 1, and the other parts are the same, thereby obtaining a water-based polyaniline anticorrosive coating DT01.
[0171] Comparative Example 3
[0172] Compared with Example 8, the difference is that 0.5 g of aluminum dihydrogen tripolyphosphate is used instead of 0.5 g of the water-based polyaniline polymer prepared in Example 1, and the other parts are the same, so as to obtain a water-based polyaniline anti-corrosion coating DT02.
[0173] The raw material formulas of water-based polyaniline anti-corrosion coatings PT01~PT06 and DT01~DT02 are summarized in Table 1.
[0174] Table 1. Raw material formula of water-based polyaniline anticorrosive coating
[0175]
[0176] Test Example 1
[0177] The water-based polyaniline anticorrosive coatings PT01-PT06, DT01 and DT02 prepared in the examples and comparative examples were sprayed on a 3 mm thick steel plate that had been sandblasted and rusted in advance. After being placed at room temperature for 7 days, the dry film thickness of the coating was 80±5 µm, and salt spray performance and adhesion performance tests were performed.
[0178] Salt spray performance test method: Tested in accordance with the national standard GB10125-2012, F-90 salt spray corrosion test machine (Qingdao Yitai Instrument Co., Ltd.); carried out in a salt spray chamber containing a sodium chloride solution with a concentration of 50g / L, the solution pH value is 6.5~7.2, and the test temperature is fixed at (35±2)℃. Salt spray resistance performance requirements: no blistering, no cracking, no shedding, no rust.
[0179] Adhesion test method: The test is carried out according to the pull-off method of GB / T5210, and the test is obtained by the pull-off method using a Positest AT-M20mm puller. Each sample is tested at least 3 points, and the adhesion data is the average value of the 3 points.
[0180] Water-based polyaniline anti-corrosion coatings PT01~PT06, DT01 and DT02 were sprayed on the tinplate polished by sandpaper. After curing at room temperature for 7 days, the dry film thickness of the coating was 80±5µm. The impact resistance and bending performance of the coating film were tested.
[0181] Paint film impact resistance test method: Test in accordance with GB / T 1732 standard.
[0182] Paint film bending performance test method: Test in accordance with GB / T 6742 standard.
[0183] The test data of the paint films formed by water-based polyaniline anti-corrosion coatings PT01~PT06, DT01 and DT02 are summarized in Table 2.
[0184] Table 2. Test data of anticorrosive coatings PT01~PT06, DT01 and DT02
[0185]
[0186] It can be seen from Table 2 that the PT01~PT06 paint films prepared in the examples have stronger adhesion than the DT01 and DT02 paint films prepared in the comparative examples and have long-lasting corrosion resistance.
[0187] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A water-based polyaniline polymer, characterized in that Having the structure of formula (I): (I); Wherein, n is an integer from 1 to 500, 0<x<1, and y is an integer from 0 to 4; R1 is selected from hydrogen, C1~C 10 Alkyl, C6~C 20 Aromatic or C6~C 20 heteroaryl; R — The acid radical ion is selected from the group consisting of ethoxy repeating units.
2. The water-based polyaniline polymer according to claim 1, characterized in that The R1 is selected from hydrogen or C1~C 10 The alkyl group; The R — Select from the following structures: 、 、 ; m is an integer from 1 to 15.
3. A method for preparing a water-based polyaniline polymer, characterized in that: include: a) an aniline compound represented by formula (II), an initiator and aluminum dihydrogen tripolyphosphate undergo a polymerization reaction to obtain a polyaniline compound; b) mixing the polyaniline compound obtained in step a) with an aqueous dopant to undergo a modification reaction to obtain an aqueous polyaniline polymer represented by formula (I); (II); The aqueous dopant is selected from acids containing ethoxy repeating units; (I); Wherein, n is an integer from 1 to 500, 0<x<1, and y is an integer from 0 to 4; R1 is selected from hydrogen, C1~C 10 Alkyl, C6~C 20 Aromatic or C6~C 20 heteroaryl; R — The acid radical ion is selected from the group consisting of ethoxy repeating units.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the aniline compound, the initiator and aluminum dihydrogen tripolyphosphate is (91-220): (67-400): (0.47-1.95); The mass ratio of the aqueous dopant to the aniline compound is 1:0.3-3.
5. A water-based anticorrosive coating, characterized in that: Comprising component A and component B; Wherein, the component A comprises the following components in parts by weight: 0.5-4 parts of the waterborne polyaniline polymer according to any one of claims 1 and 2 or the waterborne polyaniline polymer prepared by the preparation method according to any one of claims 3 and 4, 20-120 parts of waterborne epoxy resin, 5-20 parts of water, 10-30 parts of waterborne film-forming cosolvent, 5-20 parts of titanium dioxide, 8-40 parts of talc, 3-15 parts of precipitated barium sulfate, 0.3-3 parts of waterborne defoamer, and 0.4-3 parts of waterborne dispersant; The component B comprises the following components in parts by weight: 65~90 parts of water-based epoxy curing agent; 0.3~0.7 parts of anti-flash rust agent.
6. The water-based anticorrosive coating according to claim 5, characterized in that: The mass ratio of component A to component B is 1-5:
1.
7. The water-based anticorrosive coating according to claim 5, characterized in that: The waterborne epoxy resin is selected from at least one of Huntsman PZ3961-1, Shanghai Huayi STW606, Shanghai Huayi STW6521 and Shanghai Huayi STW6522.
8. The water-based anticorrosive coating according to claim 5, characterized in that: The aqueous defoamer is selected from at least one of BYK-052, BYK-088, BYK-1752, BYK-053, BYK-051, BYK-057, BYK-077, BYK-066N, BYK-392, BYK-333, BYK-141 and BYK-1790.
9. The water-based anticorrosive coating according to claim 5, characterized in that: The waterborne epoxy curing agent is selected from at least one of Huntsman AD3986, Huntsman AD3987, Huntsman AD38-1, Shanghai Huayi STW703C and Shanghai Huayi STW703D.
10. The water-based anticorrosive coating according to claim 5, characterized in that: The aqueous dispersant is selected from at least one of Disperbyk-103, Disperbyk-108, Disperbyk-115, Disperbyk-130, Disperbyk-111, Disperbyk-180, Disperbyk-160, Disperbyk-162, Disperbyk-164 and Disperbyk-182.
Citation Information
Patent Citations
Phosphate doped polyaniline anticorrosive paint and preparation method thereof
CN102108241A
Aluminum-tripolyphosphate-doped polyaniline antirust pigment and preparation method thereof
CN102226045A
Waterborne polyurethane resin, waterborne polyaniline anticorrosive paint and preparation methods thereof
CN102702467A
Ultraviolet curing anticorrosive coating
CN102702815A
Polyaniline anti-corrosive paint
CN103834265A